Lecture attendance versus academic performance and prior knowledge of accounting students: An exploratory study at a South African university - Papageorgiou, E. (South African Journal of Higher Education, 2019)
This study investigates the impact of lecture attendance on first-year Accounting students’ academic performance and whether students’ prior accounting knowledge differentially benefit from lecture attendance registered or an accounting degree at a South African university. A mixed method was exploited; quantitative, descriptive in nature and fixed effects regression model. Data was collected firstly, from the university’s central computer system and from electronic card readers installed in lecture venues. The overall findings confirm an increase in the correlations’ strength between lecture attendance and academic performance. Furthermore when the study accounted for time-invariant by means of data fixed effects estimators these effects continued and concluded that attendance-performance and prior accounting have over time a significant impact on academic performance. This paper adds to several unique contributions to accounting education confirming the importance of students’ lecture attendance and prior accounting knowledge that could influence students’ academic performance over time. Further research could add value by identifying other reasons which could influence accounting students’ academic performance registered for an accounting degree.